Co-Translational Insertion of Aquaporins into Liposome for Functional Analysis via an E. coli Based Cell-Free Protein Synthesis System - Yue, Ke (Cells, 2019)
Aquaporins are important and well-studied water channel membrane proteins. However, being membrane proteins, sample preparation for functional analysis is tedious and time-consuming. In this paper, we report a new approach for the co-translational insertion of two aquaporins from Escherichia coli and Nicotiana tabacum using the CFPS system. This was done in the presence of liposomes with a modified procedure to form homogenous proteo-liposomes suitable for functional analysis of water permeability using stopped-flow spectrophotometry. Two model aquaporins, AqpZ and NtPIP2;1, were successfully incorporated into the liposome in their active forms. Shifted green fluorescent protein was fused to the C-terminal part of AqpZ to monitor its insertion and status in the lipid environment. This new fast approach offers a fast and straightforward method for the functional analysis of aquaporins in both prokaryotic and eukaryotic organisms.